Fame, teatro e memoria. “I Cannibali” di George Tabori (Altre Modernità, 2015)
Starting from the representation of the hunger motif in Primo Levi’s If This Is a Man (It. 1947, Engl. 1959) and its variation in George Tabori’s “black mass” The Cannibals (Engl. 1968, Germ. 1969), the contribution aims to re-interpret the complex relationship of autobiographical, historical and fictional elements in the celebrated drama of the Jewish romancier and dramatist (1914-2007), who famously had “a mother tongue, Hungarian, a father tongue, English, and an uncle tongue, German”. The metadramatic structure, combined with the focus on emotional, active memory, is thus related to the intertextual medley of the play as a sign for Tabori’s search of a ‘third way’ in representing the Holocaust on the stage, moving away both from documentarian realism and sentimental celebration of the victims.